MEASUREMENT OF RENAL BIOMARKER IN PATIENTS WITH RENAL FAILURE(DIALYSIS) DIFFERENT AGE GROUPS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The kidneys play a key role in maintaining a constant internal environment. This is achieved by regulating body fluid volumes and their content in various dissolved substances, including electrolytes and various products of metabolism. With declining kidney function, these functions are wholly or partially lost. The result is a difficulty in volume regulation and the accumulation of various substances in supra-physiological concentrations. This study included(42 patient with renal failure ) that compared with 42 healthy control groups, this study was conducted in the dialysis center of Al-Rifai General Hospital in Al-Rifai city. The result of this study shown the there was a highly significant P- Value (